Development of Solid Dispersions of Clopidogrel using Innate Excipient: Synergistic Antiplatelet Activity - Verma, Chander Pal Singh; Verma, Santosh; Ashawat, Mahendra Singh; Pandit, Vinay (Indian Journal of Pharmaceutical Education and Research, 2020)
Aim: The present study encompasses on formulation and evaluation of solid dispersion of Clopidogrel, Class II drug-using pectin extracted from mango peel. Materials and Methods: Pectin was extracted from full-grown mango peel grown in the Kangra region. Solid dispersions were prepared using kneading, hot fusion method and solvent wetting method and the solvent wetting method were gauged and optimized. The prepared solid dispersions were subjected to solubility analysis and selected optimized formulation was further subjected to DSC, PXRD, in-vitro Dissolution and in-vitro antiplatelet activity. The in-vitro release studies are subjected to mathematical data analysis using DD Solver 1.0 version. Results: Extracted pectin from mango peel was light brown in color and soluble in water. The screened carriers PVPK30 and extracted pectin showed the enhanced solubility of pure drug. The pectin was further selected for the formulation of solid dispersions by three different methods. The solvent wetting method has given expected results and the formulation SD6 containing drug: pectin ratio 1:2 was selected and evaluated. The in-vitro release has shown 91.2 % in 60 min with a mean dissolution time of 14.64 min and dissolution efficiency of 0.691%. The formulation SD6 has shown 87.1 ±1.8 % antiplatelet activities whereas pure drug has shown 71.9 ±2.1% indicating enhanced activity. Conclusion: It was concluded that the pectin extracted from ripened mango peels can be a suitable carrier for the formulation of solid dispersion of clopidogrel which not only enhances the solubility but also resulted in the enhanced antiplatelet activity.
Keywords: Pectin; Solid Dispersion; Clopidogrel; DDSolver; Mean Dissolution Time